L'incidence des privilèges et des hypothèques sur le régime légal de la société d'acquêts - Robinson, Ann (Les Cahiers de droit, 1981)
Even though the partnership of acquests has been in force for over eleven years now as the official matrimonial regime in Quebec, only few legal articles and cases have considered this matter up to now. The present study attemps to fill partly this void by looking at the relationship between consorts married under this regime and their secured creditors. After an overall view of privileges and hypothecs, the author analyses the numerous situations that can arise according to whether the consorts act together or separately, according to the nature of the privileges, according to the nature of the goods, etc.